Relationship Between Parental Support And Learning Motivation - Nurlina; Amirullah (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2017)
Based on information obtained from some students in 38 public elementary schools, Gattareng, researchers found that they lacked motivation and support from their parents, so their children were also less focused on studying at home and more playing with their friends. Learning motivation is one of the factors that influence student success in teaching and learning in school. This is because each student has a different motivation between students with one another. Parental support is a very important role and is very needed by children who can support the academic achievement of children in school, one form of parental support is to give attention and help in the problems in the field of education faced by children. This study aims to determine the relationship of parental support with learning motivation in class IV and V. This type of research is a quantitative analytic study with a cross-sectional approach. With a large sample of 45 respondents. The sampling technique using total sampling method. Data analysis using a chi-square test with p-value (0.05).The results showed that respondents who said that the support of parents in the support category were 25 respondents (55.6%) and those who did not support 20 respondents (44.4%). While learning motivation in the high category was 22 respondents (48.9%) and learning motivation in the low category was 23 respondents (51.1%). This means that there is a significant relationship between the relationship of parental support with motivation to learn (p = 0.001) at the 38th elementary school. The conclusion that there is a significant relationship between the relationship of parental support with motivation to learn in class IV and V in elementary school 38 Gattareng Bulukumba district. Suggestions that parents provide support to children to be motivated to learn and get high learning achievement.